Epidemiology, Clinical Profile and Outcome of Patients of Snake Bite in Mymensingh Medical College Hospital - Miah, Md Titu; Hoque, AKM Aminul; Tarafder, Binoy Krishna; Patwary, Md Kamal Hossain; Khan, Raihan Rotap; Kabir, Shah Mohd Eftar Jahan (Journal of Bangladesh College of Physicians and Surgeons, 2010)
Snake bite is a serious global health problem. Incidence is high in Bangladesh and mortality is identified to be one of the highest in the world. Most bites are occurred by nonpoisonous snakes and as many as 40% bites inflicted by venomous snakes do not produce features of envenoming. They need supportive treatment only. Poisonous bites are treated with antivenin. But most people apply tight tourniquet and take useless and harmful treatment from traditional healers before getting admitted in hospital. Delay in diagnosis and treatment causes fatality in many cases. 46 patients admitted in department of Medicine, MMCH from April,07 to March,08 with snake bites were studied. Among them 35% were poisonous and 65% were nonpoisonous bites. Male and female ratio was 3.6:1. Mean age (years) was 34.9 ± 16.2 SD. Mean time of interval between bite and hospitalization (hours) was 7.8 ± 9.5 SD. 94% bites occurred in land and 7% in water. 100% patients applied multiple tourniquets in the affected limb. 24% patients received treatment from traditional healers with development of cellulitis in 64% of them. None received proper first aid management. Most incidences were in July - August. Snakes could not be identified in 50% poisonous and 77% non-poisonous cases. Among the identified poisonous snakes, kraits were 84%. Clinical features were also suggestive of krait bite in 88% poisonous cases. Among poisonous cases, 94% presented with neurological manifestation and ptosis was present in all of them. 75% poisonous snake-bite patients received antivenin and none of them developed anaphylaxis. Among 4 poisonous snake bite patients who did not receive antivenin, 2 survived. Mortality in poisonous cases was 44%. All of the non-poisonous cases improved with supportive treatment. DOI: 10.3329/jbcps.v27i2.4249 J Bangladesh Coll Phys Surg 2009; 27: 70-75